Combined effects of gender affirmation and economic hardship on vulnerability to HIV: a qualitative analysis among U.S. adult transgender women - Larissa Jennings Mayo-Wilson; Eric G. Benotsch; Sheila R. Grigsby; Sarah Wagner; Fatmata Timbo; Tonia Poteat; Lauretta Cathers; Ashlee N. Sawyer; Shelby A. Smout; Rick S. Zimmerman (BMC, 2020)
Abstract Background Transgender women ("trans women"), particularly African-American and Latina trans women, have disproportionately high prevalence of HIV in the United States (U.S.). In order to decrease gender dysphoria and overcome discrimination, trans women affirm their gender through social and medical transition, often in contexts of economic hardship and sexual risk. This study qualitatively examined how gender-affirming behaviors enhance or diminish vulnerability to HIV in light of structural and economic barriers to gender transition. Methods We conducted individual interviews with 19 adult trans women in two U.S. cities (Richmond, VA and St. Louis, MO) who reported one or more sexual risk behaviors and recent economic hardship related to employment/income, housing, or food security. Interviews were recorded, transcribed, and analyzed using thematic content analysis. Results The majority (74%) of trans women were racial/ethnic minorities with mean age of 26.3 years. Gender-affirming behaviors varied with 58% of trans women having legally changed their name and gender marker; 79% having initiated hormone therapy; and 11% having not initiated any medical or legal changes. None had undertaken surgical changes. Findings suggested that the process of gender transitioning resulted in both increasing and decreasing HIV risk. The high need for gender affirmation by male sex partners contributed to trans women's exposure to sexual objectification, sexual risk behaviors, and conflicting interests in HIV prevention messaging. Loss of housing and employment due to transition along with the high costs of transition products and medical visits increased reliance on sex work and created new obstacles in accessing HIV services. Trans women experienced lower HIV risk as they acquired legal and medical transition services, reshaped interactions with sex partners, and received gender-affirming support by others, including health providers, employers, peers, and housing professionals. Sexual abstinence was viewed as a negative consequence of incomplete transition, although characterized as a period of low HIV risk. Conclusions Structural and policy initiatives that promote safe gender transition and economic stability in trans women may play a critical role in reducing HIV in this population. Addressing the harmful pressures for U.S. trans women to conform to perceived feminine stereotypes may also serve an important role.